Dampak ekonomi kreatif terhadap motivasi belajar siswa - Syifa Haliza; Trisni Handayani (Curricula: Journal of Curriculum Development, 2026)
Innovative learning strategies to enhance student engagement in vocational education are urgently needed. This study aims to analyze the impact of the creative economy on student motivation for learning in the Visual Communication Design (Desain Komunikasi Visual or DKV) program. A quantitative approach was employed using a survey, with 45 respondents selected through saturation sampling. Data were collected via a Likert-scale questionnaire and analyzed using descriptive statistics, validity and reliability tests, and simple linear regression. The results indicate a positive and significant relationship between the implementation of the creative economy and student learning motivation. These findings indicate that integrating creative economy-based projects into the learning process can enhance students’ intrinsic and extrinsic motivation, strengthen their engagement, and provide meaningful learning experiences aligned with industry needs. This study contributes to strengthening the theoretical foundation of creative economy practices in vocational education and encourages further research with broader variables and mixed-methods approaches.